Cocoa Farmers and Agrochemical Safety Compliance: Empirical Insights from Ghana - Tham-Agyekum, Enoch Kwame; Ankuyi, Fred; Jones, Ebenezer Osei; Tierku, Albert Kuuzaa; Sarfo, Derrick Kwadwo; Bakang, John-Eudes Andivi; Amoako, Prince Kwadwo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
This study addresses the lack of empirical insights into the adherence of cocoa farmers to safety protocols. Specifically focused on agrochemical safety compliance, the research employs a quantitative approach and collects data from 385 cocoa farmers in the Nzema East Municipal through a structured questionnaire. The analysis utilizes mean, standard deviation, frequency, percentages, and Tobit regression models. The study finds that cocoa farmers exhibit a high level of knowledge and preparedness in agrochemical handling practices, positive agrochemical usage practices, and proper agrochemical storage practices. Cocoa farmers employ integrated pest management strategies, using diverse fertilizers, insecticides, fungicides, and herbicides to address crop health and productivity challenges. Tobit regression results showed that the extent of use of agrochemicals was significantly influenced by marital status, household size, farming experience, cooperative membership, and access to spraying machines and personal protective equipment. The research highlights the importance of integrating safety considerations into agricultural policies and practices, emphasizing the role of knowledge and awareness in influencing farmers' practices. It suggests the need for targeted interventions and educational programs to enhance agrochemical safety compliance among cocoa farmers.